Determination of Spearman Correlation Coefficient (r) to Evaluate the Linear Association of Dermal Collagen and Elastic Fibers in the Perspectives of Skin Injury - Naveen Kumar; Pramod Kumar; Satheesha Nayak Badagabettu; Melissa Glenda Lewis; Murali Adiga; Ashwini Aithal Padur (Dermatology Research and Practice)
Background. Difference in scar formation at different sites, in different directions at the same site, but with changes in the elasticity of skin with age, sex, and race or in some pathological conditions, is well known to clinicians. The inappropriate collagen syntheses and delayed or lack of epithelialization are known to induce scar formation with negligible elasticity at the site of damage. Changes in the elasticity of scars may be due to an unequal distribution of dermal collagen (C) and elastic (E) fibers. Materials and Methods. Spearman correlation coefficients (r) of collagen and elastic fibers in horizontal (H) and in vertical (V) directions (variables CV, CH, EV, and EH) were measured from the respective quantitative fraction data in 320 skin samples from 32 human cadavers collected at five selected sites over extremities. Results. Spearman’s correlation analysis revealed the statistically significant (p<0.01) strong positive correlation between CH and CV in all the areas, that is, shoulder joint area (r=0.66), wrist (r=0.75), forearm (r=0.75), and thigh (r=0.80), except at the ankle (r=0.26, p=0.14) region. Similarly, positive correlation between EH and EV has been observed at the forearm (r=0.65, moderate) and thigh (r=0.42, low) regions. However, a significant moderate negative correlation was observed between CV and EV at the forearm (r=-0.51) and between CH and EH at the thigh region (r=-0.65). Conclusion. Significant differences of correlations of collagen and elastic fibers in different directions from different areas of extremities were noted. This may be one of the possible anatomical reasons of scar behavior in different areas and different directions of the same area.